Who were the first North Americans? - Wingate, Philippa; Reid, Struan; Cuzik, David (London : Usborne ; Tulsa, OK : EDC, 2003)
An introduction to the early North American Natives, discussing their origins, way of life, and contact with Europeans. Includes Internet links to addition information.
First published: 1995.
Includes index.
3.5
K-3
Keywords: Indians of North America -- Juvenile literature; Indians of North America; Native Americans -- North America